DCAV: A software system to evaluate next‐generation cloud data center availability through a friendly graphical interface. (11th September 2019) - Moreira, Andre; Rosendo, Daniel; Gomes, Demis; Leoni Santos, Guto; Silva, Leylane; Cani, Carolina; Kelner, Judith; Sadok, Djamel; Gonçalves, Glauco; Mehta, Amardeep; Wildeman, Mattias; Takako Endo, Patricia
Summary: To assess the availability of different data center configurations, understand the main root causes of data center failures and represent its low‐level details, such as subsystem's behavior and their interconnections, we have proposed, in previous works, a set of stochastic models to represent different data center architectures (considering three subsystems: power, cooling, and IT) based on the TIA‐942 standard. In this paper, we propose the Data Center Availability (DCAV), a web‐based software system to allow data center operators to evaluate the availability of their data center infrastructure through a friendly interface, without need of understanding the technical details of the stochastic models. DCAV offers an easy step‐by‐step interface to create and configure a data center model. The main goal of the DCAV system is to abstract low‐level details and modeling complexities, becoming the data center availability analysis a simple and less time‐consuming task.